2017
DOI: 10.1128/mbio.00671-17
|View full text |Cite
|
Sign up to set email alerts
|

Disguised as a Sulfate Reducer: Growth of the Deltaproteobacterium Desulfurivibrio alkaliphilus by Sulfide Oxidation with Nitrate

Abstract: This study demonstrates that the deltaproteobacterium Desulfurivibrio alkaliphilus can grow chemolithotrophically by coupling sulfide oxidation to the dissimilatory reduction of nitrate and nitrite to ammonium. Key genes of known sulfide oxidation pathways are absent from the genome of D. alkaliphilus. Instead, the genome contains all of the genes necessary for sulfate reduction, including a gene for a reductive-type dissimilatory bisulfite reductase (DSR). Despite this, growth by sulfate reduction was not obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 27 publications
7
138
0
Order By: Relevance
“…Sulfide might be used by the reverse reaction of the sulfate reduction pathway; however, when we analyzed the phylogenetic relationship of the relevant DsrA protein encoded by these organisms, we noted that it falls into the sulfate-reducing and not the sulfideoxidizing cluster, making it unlikely that these bacteria are able to oxidize sulfide with DsrAB. It has however recently been reported that a reductive-type DsrAB might be able to work in the oxidative direction (Thorup et al, 2017), but this result has not yet been biochemically validated. We did not find a sulfide quinone oxidoreductase that could complement this activity, making it unlikely that sulfide is used as an electron donor.…”
Section: Discussionmentioning
confidence: 97%
“…Sulfide might be used by the reverse reaction of the sulfate reduction pathway; however, when we analyzed the phylogenetic relationship of the relevant DsrA protein encoded by these organisms, we noted that it falls into the sulfate-reducing and not the sulfideoxidizing cluster, making it unlikely that these bacteria are able to oxidize sulfide with DsrAB. It has however recently been reported that a reductive-type DsrAB might be able to work in the oxidative direction (Thorup et al, 2017), but this result has not yet been biochemically validated. We did not find a sulfide quinone oxidoreductase that could complement this activity, making it unlikely that sulfide is used as an electron donor.…”
Section: Discussionmentioning
confidence: 97%
“…Nitrate is reduced to ammonia rather than denitrified to N 2 and, therefore, this nutrient remains available for the sediment microbial community. Remarkably, even some sulfate-reducing bacteria contribute to the oxidation of sulfide with nitrate by inversing the pathway of dissimilatory sulfate reduction (Thorup et al, 2017). Similar as Beggiatoa, Desulfurivibrio alkaliphilus oxidizes sulfide initially to elemental sulfur, which is subsequently oxidized to sulfate.…”
Section: Cable Bacteria and The Sulfur Cyclementioning
confidence: 99%
“…, Thorup et al . ). Importantly, catalytic directionality is generally consistent with phylogenetic placement of DsrAB (Müller et al .…”
Section: Resultsmentioning
confidence: 99%
“…5). DsrAB functions in both the forward (SO 4 2− reduction) and reverse (S oxidation) directions and may also be potentially involved in S /polysulfide disproportionation (Müller et al 2014, Thorup et al 2017. Importantly, catalytic directionality is generally consistent with phylogenetic placement of DsrAB (Müller et al 2015).…”
Section: Taxonomic and Functional Composition Of The Ep Sediment Commmentioning
confidence: 97%